# 1.13

Revision as of 12:18, 1 September 2020 by Algowikiadmin (talk | contribs) (Created page with "The basis case is when <math>n = 0</math><br> :<math>\sum_{i=1}^0 i^2 = 0^2 = 0 </math><br> and using <math>n=0</math> in the formula <math>\frac {n(n + 1)(2 \cdot n + 1)} {6}...")

The basis case is when

and using
in the formula
you get:

Since these are equal, the basis case is true.

Now, I will show that on the assumption that the summation is true for *n*, it follows that it is true for

Which should be equal to the formula when :

Back to Chapter 1.